PEMBINAAN PENGELOLA USAHA DAYA TARIK WISATA DI JAWA TENGAH: SOSIALISASI STANDAR USAHA - Aurilia Triani Aryaningtyas; Aletta Dewi Maria Th (Institut Teknologi Dirgantara Adisutjipto, 2021)
Central Java is one of the tourism destinations in Indonesia that offers a variety of amazing tourist attractions. However, the current tourism attraction business managers are still facing problems including: the problem of structuring, managing, and developing tourist attraction that is still not in accordance with established standards. Therefore, in the dedication of the Community Activities, the executor of dedication implementer conducts socialization and coaching to increase understanding and ability in managing tourist attraction businesses, to comply with specified standards, as well as understanding procedures to obtain tourism business certification. The activities include: 1) Presentation of material about Tourism Business, 2) Presentation of material about Standards for Management of Tourism Attractions and how to obtain certification, 3) Discussion.